2014
DOI: 10.1371/journal.pone.0105583
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Longer Habitual Day Napping and Non-Alcoholic Fatty Liver Disease in an Elderly Chinese Population

Abstract: ContextBoth longer habitual day napping and Non-Alcoholic Fatty Liver Disease (NAFLD) are associated with diabetes and inflammation, but the association between day napping and NAFLD remains unexplored.ObjectiveTo investigate the association between the duration of habitual day napping and NAFLD in an elderly Chinese population and to gain insight into the role of inflammatory cytokines in this association.Design and SettingWe conducted a series of cross-sectional studies of the community population in Chongqi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
2
17
1
Order By: Relevance
“…A longer daytime nap duration (>0.5 h) was significantly associated with a higher risk of prevalent NAFLD. A similar study by Qu et al reported the same finding . In that study, the diagnostic criterion for NAFLD primarily depended on an FLI >60.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A longer daytime nap duration (>0.5 h) was significantly associated with a higher risk of prevalent NAFLD. A similar study by Qu et al reported the same finding . In that study, the diagnostic criterion for NAFLD primarily depended on an FLI >60.…”
Section: Discussionsupporting
confidence: 73%
“…A similar study by Qu et al reported the same finding. 34 In that study, the diagnostic criterion for NAFLD primarily depended on an FLI >60. However, approximately 30% of patients have indeterminate results for the diagnosis of NAFLD, with an FLI score between cut-off values (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…53 A sedentary behaviour might act as an independent risk factor for NAFLD 54 and lower levels of physical activity are found in patients with NAFLD. 57 Maintenance of ideal weight or weight loss in overweight/obese patients via lifestyle interventions has become an established strategy also to prevent or treat NAFLD, 52,58,59 although the goal might be difficult to achieve in the ambulatory care setting. 57 Maintenance of ideal weight or weight loss in overweight/obese patients via lifestyle interventions has become an established strategy also to prevent or treat NAFLD, 52,58,59 although the goal might be difficult to achieve in the ambulatory care setting.…”
Section: Nonalcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…55,56 Also, reduced physical activity such as longer habitual day napping was independently associated with NAFLD. 57 Maintenance of ideal weight or weight loss in overweight/obese patients via lifestyle interventions has become an established strategy also to prevent or treat NAFLD, 52,58,59 although the goal might be difficult to achieve in the ambulatory care setting. 60 Reducing weight by ≥10% can contribute to the nonalcoholic steatohepatitis (NASH) resolution and fibrosis improvement, while a modest weight loss >5%-7% also produces important benefits on the components of the NAFLD activity score.…”
Section: Nonalcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…Recently, daytime napping has been linked with a series of adverse health outcomes, including nonalcoholic fatty liver disease [10], diabetes mellitus [2,11], breast cancer [12], and mortality [9,13]. The napping-mortality association has received significant attention, but it remains controversial.…”
Section: Introductionmentioning
confidence: 99%